PROPRANOLOL AS FIRST-LINE TREATMENT OF INFANTILE HEMANGIOMAS - Pereira, Joana (2014)
Background: Hemangiomas are the most common vascular tumors of infancy. In approximately 10% of patients occur complications that obligate to intervene. Propranolol was recently added to the list of drugs available to treat these patients, and has been changing the therapeutic attitude towards these lesions. This study objective is to evaluate propranolol efficacy and safety in the treatment of infantile hemangiomas.Material and Methods: This is a retrospective descriptive study of patients treated with propranolol, between March 2010 and March 2013. The candidates for treatment were patients with proliferative phase hemangiomas with rapid growth or functional or aesthetic compromise. It was performed as an ambulatory treatment and the dosage used was 2mg/kg per day. Treatment response was categorized in complete, partial or absent.Results: We treated 22 patients, with a total of 32 hemangiomas. The main indications for treatment were the aesthetic (n=18) and functional risks (n=9). We observed a growth stabilization of hemangiomas in all cases. Regression was total in 20 cases and partial in three, which corresponds to a therapeutic success of 87%. Four patients are still on therapy and in one case we had to stop the drug prematurely due to bradycardia.Discussion and Conclusion: In the majority of cases propranolol caused a rapid and maintained regression of hemangiomas, shortening the natural duration of lesions, with few side effects. We consider propranolol the first line therapy for hemangiomas in infancy.